Lifestyle Interventions Limit Gestational Weight Gain in Women with Overweight or Obesity: LIFE‐Moms Prospective Meta‐Analysis. Issue 9 (6th September 2018) - Peaceman, Alan M.; Clifton, Rebecca G.; Phelan, Suzanne; Gallagher, Dympna; Evans, Mary; Redman, Leanne M.; Knowler, William C.; Joshipura, Kaumudi; Haire‐Joshu, Debra; Yanovski, Susan Z.; Couch, Kimberly A.; Drews, Kimberly L.; et al.
Abstract: Objective: This study aimed to evaluate the effects of varied lifestyle intervention programs designed to ameliorate excess gestational weight gain (GWG) in pregnant women with overweight or obesity compared with standard care, including effects on pregnancy outcomes. Methods: Seven clinical centers conducted separate randomized clinical trials to test different lifestyle intervention strategies to modify GWG in diverse populations. Eligibility criteria, specific outcome measures, and assessment procedures were standardized across trials. The results of the separate trials were combined using an individual‐participant data meta‐analysis. Results: For the 1, 150 women randomized, the percent with excess GWG per week was significantly lower in the intervention group compared with the standard care group (61.8% vs. 75.0%; odds ratio [95% CI]: 0.52 [0.40 to 0.67]). Total GWG from enrollment to 36 weeks' gestation was also lower in the intervention group (8.1 ± 5.2 vs. 9.7 ± 5.4 kg; mean difference: −1.59 kg [95% CI:−2.18 to −0.99 kg]). The results from the individual trials were similar. The intervention and standard care groups did not differ in preeclampsia, gestational diabetes, cesarean delivery, or birth weight. Conclusions: Behavioral lifestyle interventions focusing primarily on diet and physical activity among women with overweight and obesity resulted in a significantly lower proportion of women with excess GWG. This modest beneficial effect was consistent across diverse intervention modalities in a large, racially and socioeconomically diverse US population of pregnant women.